ANALISIS KONFLIK BATIN TOKOH DALAM NOVEL CINTA-MU SELUAS SAMUDRA KARYA GOLA GONG: PSIKOLOGI SASTRA - Lamalian, Wehelmina Junita; Priyadi, Antonius Totok; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe background of this research is based on the researcher’s interest about the characters’ internal conflict in the novel Cinta-Mu Seluas Samudra by Gol A Gong. Internal conflict occurs because of the individuals are unable or untrained in controlling their emotions, common sense, or mind and conscience toward their problems in life. As for the research problem, it is the internal conflict in the novel Cinta-Mu Seluas Samudra by Gol A Gong that every character experiences. The research method used is descriptive with qualitative design and behavioristic approach. The research data are words or phrases, sentences and paragraphs that depict the formulation of problems in this research. The source of data is the novel Cinta-Mu Seluas Samudra and the research tool which is the researcher as main instrument. The result of this research is that internal conflict of the main and side characters that comprises of pent-up guilt/guilt, self-condemnation, shame, sadness, hatred, fear, regret, stress, hope, confusion, anxiety, upset, heartache, jealousy, trauma, heartbreak, dislikeness and anger. This research may be used as a reference to teaching material for Indonesian language teacher at the second semester in twelfth grade foor KD 3.9 and KD 4.9. The suggestion for next research is to analyze other aspects such as educational values in this novel.Keywords: Analysis, Internal Conflict, Novel